2021
DOI: 10.1002/etc.4982
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Quantitative Measurements of Radical Production by Photocatalytic TiO2 with Daphnia magna Toxicity

Abstract: Increased use of titanium dioxide (TiO2) nanoparticles (NPs) in domestic and industrial applications has increased the risk for adverse environmental outcomes based on an elevated likelihood of organism exposure. Anatase TiO2 NP exposure to ultraviolet A (UV‐A) radiation in aquatic environments generates radical oxygen species (ROS), which may ultimately be responsible for increased organism toxicity. We have identified and measured the 2 most relevant ROS species, hydroxyl and superoxide radicals, and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Coral et al (2021) indicated that ROS production is positively correlated with the increasing of TiO 2 concentration and UV‐A intensity. Because most toxicity data collected for EF derivatives were based on laboratory exposures and lacked the consideration of realistic freshwater exposures.…”
Section: Resultsmentioning
confidence: 99%
“…Coral et al (2021) indicated that ROS production is positively correlated with the increasing of TiO 2 concentration and UV‐A intensity. Because most toxicity data collected for EF derivatives were based on laboratory exposures and lacked the consideration of realistic freshwater exposures.…”
Section: Resultsmentioning
confidence: 99%
“…25 Some research suggests that the structure of anatase can destroy a bacterial membrane and cell wall by generating negative hydroxyl free radicals ( * OH) in a photocatalytic reaction. 26 These properties are clearly explained in the below section.…”
Section: Synthesis Of Metal/metal Oxide Npsmentioning
confidence: 86%
“…So, after staining platelets with DHR123, the increment in fluorescence of R123, as continuously recorded (λ ex/em = 485/528 nm) by a plate reader (BMG LABTECH, Germany), is proportional to the rate of mtROS generation [ 28 ]. For each sample, the average rate of mtROS generation is expressed as the slope of a linear regression line fitted to the fluorometric data [ 29 ].…”
Section: Methodsmentioning
confidence: 99%